Raising Keynes : a twenty-first-century general theory - Marglin, Stephen A. (Harvard University Press, 2021)
"John Maynard Keynes's General Theory of Employment, Interest, and Money was the most influential economic idea of the twentieth century. But, argues Stephen Marglin, its radical implications were obscured by Keynes's lack of the mathematical tools necessary to argue convincingly that the problem was the market itself, as distinct from myriad sources of friction around its margins. Marglin fills in the theoretical gaps, revealing the deeper meaning of the General Theory. Drawing on eight decades of discussion and debate since the General Theory was published, as well as on his own research, Marglin substantiates Keynes's intuition that there is no mechanism within a capitalist economy that ensures full employment. Even if deregulating the economy could make it more like the textbook ideal of perfect competition, this would not address the problem that Keynes identified: the potential inadequacy of aggregate demand."--